Real Behaviour and Remaining Lifetime of Bridge Structures - Josef Vican; Jozef Gocal; Branislav Melis; Peter Kotes; Patrik Kotula (Communications - Scientific letters of the University of Zilina, 2008)
The paper presents results of research activities of the Department of Structures and Bridges in the field of investigation of the real behaviour, reliability and durability of existing bridge structures. There are introduced two cases of these research activities in the paper having significant effects on the determining bridge remaining lifetime, which is the basic information from the viewpoint of bridge rehabilitation. The third presented research activity is devoted to the possibility of bridge RC beams strengthening using the FRP lamellas and strips from the viewpoint of determining the resistance of the strengthened RC beams.